The influence of Business Intelligence capacity, network learning and innovativeness on startups performance - Nuno Caseiro; Arnaldo Coelho (Journal of Innovation & Knowledge (JIK), 2019)
This paper proposes a model to investigate the direct effects of Business Intelligence (BI) on performance, and the indirect effects, through network learning (NL) and innovativeness (INNOV). The investigation is based on a sample of 228 startups from different European countries. We explore those relationships using Structural Equation Modeling. The results of this study point to positive effects among the different variables and we can conclude that Business Intelligence capacities have an impact on network learning, innovativeness and performance. From these findings, it can be argued that some attention must be made to the business intelligence capacities in startups, given the impact it can have on firm performance. Also, the network learning effect through BI is significative and presents a positive influence in performance. As startups usually are struggling with lack of resources and the team faces multiple attention demands it seems that proposing business intelligence practices is a new challenge to overcame, but as information is a key resource for better decision making it can payoff.
Keywords: M13; L26; L10; D83; 650; Business intelligence; Entrepreneurship; Innovativeness; Network learning; Startups